The Jefferson Manual for Neurocritical Care - Jallo, Jack; Urtecho, Jacqueline S. (Thieme, 2021)
The quintessential reference for bedside medical management of neurocritical care patients Medical management of patients in the neurocritical care unit (NCCU) often spells the difference between life or death and return to normal function or a lifetime disability. As such, it is vital that patients with life-threatening neurological and neurosurgical illnesses receive prompt diagnosis and rapid interventions in the NCCU. The Jefferson Manual for Neurocritical Care by renowned neurosurgeon Jack I. Jallo, neurointensive care physician Jacqueline S. Urtecho, and distinguished colleagues is a hig